Evaluating the Passivation Layer of Freshly Cleaved Silicon Surfaces by Binary Silane‐Based Electrolytes. Issue 10 (5th July 2021) - Schneier, Dan; Horowitz, Yonatan; Kasnatscheew, Johannes; Grünebaum, Mariano; Wiemhöfer, Hans‐Dieter; Winter, Martin; Peled, Emanuel
Abstract: The expansion of silicon anodes in lithium‐ion batteries during lithiation and the resulting instability of its solid‐electrolyte interphase (SEI) has been its Achilles heel for quite some time. Beyond the mechanical damage, this expansion exposes fresh elemental silicon to the electrolyte solution. The electrolyte readily decomposes on the reactive silicon surface. Researchers that test novel electrolytes find it difficult to separate which of the electrolyte components (solvent or anion) decomposes first and diagnose the respective decomposition products. Here, we utilize a straightforward test protocol that reveals which reduces first on bare silicon. We exposed four electrolyte mixtures to elemental silicon in custom made T‐cells by breaking thin silicon wafers in solution. We analyze the resulting surface film layers and compare their composition to the electrolyte's performance in symmetrical lithium cells, and Si/Li cells. We found that unstable anions rather than reactive solvents lead to poor electrochemical performance. Abstract : Decomposition race : The expansion of Si in Li‐ion batteries during lithiation exposes the electrolyte to reactive Si facets. Consequently, the electrolyte decomposes. But which reduces first: the solvent or salt? Here, by monitoring the voltage behavior of cleaved wafers inside a Si/Li cell, and ex situ surface analysis we suggest that unstable anions rather than reactive solvents lead to poor electrochemical performance.